Nuevas técnicas de estudios de usuario aplicadas a bibliotecas - Riaza Chaparro, Maribel (Revista General de Información y Documentación, 2008)
Since its early stages, at the end of 70’s, O. S. Caja Madrid libraries has been progressively adapted to Society evolution (changes). Therefore, users research has been used as a worthy tool to fit the services that these libraries offer to its members. Throughout 2007, O. S. Caja Madrid has been a pioneering in Spain, in the use of “Mystery Shopper” (a pretended member) technique in this field, as an objective way of getting information about its quality libraries services.